Constructing Digital Selves: A Narrative Review on Identity in Online Communities - Putra, M. Nuur Tanja (Indonesian Scientific Publication, 2024)
In the digital era, identity construction has become increasingly intertwined with online interactions and platform-based communication. This narrative review aims to synthesize contemporary findings on how individuals construct and express identities within diverse online communities. Utilizing qualitative and quantitative studies retrieved from Scopus, PubMed, and Google Scholar, the review focuses on four primary contexts: social media platforms, online activism, role-playing games, and professional networking sites. Keywords such as